Effectiveness of dexamethasone and hyaluronidase + valerate of bethasone associated with prepucial massage in the treatment of child phimosis - Rocha, Anna Karoline da; Meyer, Karine Furtado (Journal of Clinical Nephrology, 2019)
Introduction: The phimosis condition is characterized by the inability to retract the foreskin on the glans, making it impossible to expose them. Surgical treatment, although effective, has been questioned by the risk to which the patient is exposed. Therefore, we have opted for the use of topical corticosteroids to resolve this pathology. Goals: To compare the effectiveness of Dexamethasone and Hyaluronidase + Betamethasone Valerate associated with preputial massage in the treatment of infantile phimosis, the degree of regression of phimosis, the time needed to achieve complete efficacy, possible adverse reactions, long-term outcome and parental adherence to treatment in children attending a specialized service in Blumenau, Santa Catarina. Materials and methods: Controlled clinical trial, quantitative, non-blind, prospective and randomized sample analysis through the analysis of 523 patients. Results: After 1 month of treatment, 435 patients presented some degree of regression and 63 children were referred to surgery. The success rate in this period was 45.8% in boys who were taking Hyaluronidase + Betamethasone Valerate and 49.8% in those who used Dexamethasone. In the late evaluation, 398 children reached grade 0, and 213 used Hyaluronidase + Betamethasone Valerate and 185, Dexamethasone; 39 patients were referred to the postectomy. Adherence to treatment was similar in both groups. The average time for degree 0 to be reached similar in both. Conclusion: Both topical corticosteroids were effective in the resolution of phimosis. However, in the evaluation after the first month and in the regression, Dexamethasone proved to be more effective. The time to resolution of the condition was similar for both. The surgical procedure was taken when there was no clinical improvement. No adverse effects were reported in both groups.